Radical Diazidation of Alkenes: Cu/Fe/Mn Catalysis and Electrochemical Support. Issue 9 (7th March 2018) - Ahmed, Nisar; Khatoon, Saira; Shirinfar, Bahareh
Abstract: The synthetic routes for C‐N3 bond formation through a radical mechanism with the use of transition metals provide efficient diazide products, which can be further applied in many transformations to synthesize various valuable nitrogen‐containing compounds of pharmaceutical interest. The reported methods evidence stoichiometric heavy metals and toxic reagents (as N3 ‐source) and generally exhibit a limited substrate scope. However, the electrochemical diazidations are found to be environmentally friendly and very simple, while also providing a highly efficient way to synthesize 1, 2‐diazide derivatives. Moreover, they provide a smart alternative for easy access to 1, 2‐diamines, which can be used for future modern syntheses. Abstract : A simple and friendly method : The synthetic routes for C−N3 bond formation through a radical mechanism with the use of transition metals provide efficient diazide products, which can be further applied in many transformations to synthesize various valuable nitrogen‐containing compounds of pharmaceutical interest. The reported methods evidence stoichiometric heavy metals and toxic reagents (as N3 ‐source) and generally exhibit a limited substrate scope. However, the electrochemical diazidations are found to be environmentally friendly and very simple, while also providing a highly efficient way to synthesize 1, 2‐diazide derivatives. Moreover, they provide a smart alternative for easy access to 1, 2‐diamines, which can be used for future modern syntheses.